A systematic mapping literature review of education around sexual and gender diversities - López-Orozco, Christian Fernando; López-Caudana, Edgar Omar; Ponce, Pedro (Frontiers in Sociology, 2022)
The teaching of sexual and gender identities is highly important to understand diversity and prevent social issues, discrimination, violence and even murder. Nevertheless, educational institutions around the world are lacking a curriculum that includes diversity at its best and acknowledges the LGBTQ+ community, which is one of the minorities that faces consequences from this exclusion. This paper presents a detailed description of the process applied to analyze the studies using a systematic mapping literature review, as well as the results found from those educational institutions that started their path to inclusion around sexual and gender diversities through their curricula. The research questions targeted on this work are: What is being taught in educational institutions regarding sexual and gender diversities? What are the approaches used inside the classrooms to teach sexual and gender diversities? Which students are receiving education regarding sexual and gender diversities? Is there a technological approach and/or tool used to teach sexual and gender diversities? After applying the filtering processes 69 studies were selected from five different online libraries: ACM, DOAJ, Lens.org, SCOPUS and SpringerLink. The conclusions made from the findings of this work are that those studies that do tackle concerns around the topic have proven to benefit the LGBTQ+ community, the education around sexual and gender diversities predominates within the healthcare field, there is a lack of studies around this topic in Latin-American countries and that technological tools are minimally used during the teaching processes. Finally, this work presents a call of action to educational institutions to increase their efforts around diversity.